2019
DOI: 10.1177/8756479319879076
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Vasa Previa in a Velamentous Cord Insertion Identified During Sonographic Examination

Abstract: Vasa previa is a life-threatening complication of a velamentous cord insertion. Understanding variations of this condition is vital to ensuring optimal patient outcomes. The case presented is of a 27-year-old primigravida woman whose condition was diagnosed during her second-trimester obstetric sonographic examination. The case demonstrated an unusual variation of vasa previa, in which a single fetal vessel separated from the membranous insertion located near the fundal placenta and traversed posteriorly throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition to the two well-described categories of VP, a third phenotype was reported recently, characterized by aberrant vessels leaving the placental surface and subsequently returning to the placental mass with a 'boomerang orbit', in the absence of a velamentous cord insertion or a bilobed/succenturiate placenta (Figure 5) 9,10,29,30 . In view of our findings, we would like to challenge this definition of Type-III VP: the presence of a velamentous cord insertion or succenturiate lobes does not define per se VP Type I and Type II, respectively, since aberrant vessels of Type-III VP can coexist along with placental or cord abnormalities, as long as these structures are not adjacent to the internal os and the aberrant vessel represents the only vascular structure in the lower uterine segment 12,[24][25][26] .…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the two well-described categories of VP, a third phenotype was reported recently, characterized by aberrant vessels leaving the placental surface and subsequently returning to the placental mass with a 'boomerang orbit', in the absence of a velamentous cord insertion or a bilobed/succenturiate placenta (Figure 5) 9,10,29,30 . In view of our findings, we would like to challenge this definition of Type-III VP: the presence of a velamentous cord insertion or succenturiate lobes does not define per se VP Type I and Type II, respectively, since aberrant vessels of Type-III VP can coexist along with placental or cord abnormalities, as long as these structures are not adjacent to the internal os and the aberrant vessel represents the only vascular structure in the lower uterine segment 12,[24][25][26] .…”
Section: Discussionmentioning
confidence: 90%
“…11 While sonography is often the preferred single imaging modality for evaluating for PAS, the accuracy for diagnosing it remains higher when both sonography and MRI are conducted together (97.5%). 2,13…”
Section: Discussionmentioning
confidence: 99%
“…11 While sonography is often the preferred single imaging modality for evaluating for PAS, the accuracy for diagnosing it remains higher when both sonography and MRI are conducted together (97.5%). 2,13 It is important to note that sonography has technical limitations and user dependency leading to inaccuracies of diagnosing PAS. 2 It has been shown that second trimester sonographic findings associated with the misdiagnosis of PAS included abdominal fat, bladder fullness, and placental location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations